INOVASI PEMBERDAYAAN PEREMPUAN DI DESA MARGA KAYA: PELATIHAN PEMBUATAN PERMEN JAHE UNTUK MENGEMBANGKAN UMKM - Niar Azriya; Safitri, Meilinda; Faithya, Kinanti Nurul; Gaol, Rotua Astrina Lumban; Nuzleha (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2025)
The training on ginger candy making conducted in Marga Kaya Village has the important objective of empowering women in the village through innovation in ginger products. This initiative is a strategic step to support the development of Micro, Small and Medium Enterprises (MSMEs) in the region. In this activity, a total of 15 participants were involved with an interactive approach, which included theoretical learning as well as hands-on practice. The training process started from the selection of raw materials to the development of effective marketing strategies. One of the innovations introduced during the training was a product called JJ Bear, a ginger candy designed with an attractive and child-friendly appearance. In addition, the training also served to increase participants' understanding of the various health benefits contained in ginger. More than just knowledge, the participants were also equipped with practical skills in making products based on natural ingredients, which is expected to encourage the economic independence of the local community. The results of the training showed a high level of enthusiasm among the participants, as well as great potential to utilize ginger as a marketable product. Thus, it is hoped that this initiative can not only improve individual welfare, but also contribute to the sustainable development of the local economy.